ANTICANCER ACTIVITY OF MANGOSTEEN PERICARP DRY EXTRACT AGAINST MCF-7 BREAST CANCER CELL LINE THROUGH ESTROGEN RECEPTOR -α - Setiawati, Agustina (Indonesian Journal of Pharmacy, 2014)
Breast cancer has very complex morphological and molecular characteristic. Estrogen receptor is one of biomarker in breast cancer progression, more than 60% breast cancer overexpress estrogen receptor α (ERα). Xanthone in Garcinia mangostana was investigated whether to have anticancer activity on colorectal, prostate, lung, blood and breast cancer. This research was focused on molecular mechanism of anticancer activity of mangosteen pericarp extract (MPE) on ER-α. This study used MCF-7 cells as a model of ER-α overexpressed breast cancer cells. Cytotoxic study towards MCF-7 cells was designed by using MTT test, further apoptotic induction assay was determined by double staining method using acridine orange and ethidium bromide. Extract molecular mechanism against breast cancer was assayed by immunocytochemistry. The MTT data was analyze using probit analysis to get IC50 then apoptosis and immunocytochemistry data were analysis qualitative analysis. MPE had strong cytotoxic activity on MCF-7 cells with IC50 of 45μg/mL and morphological changes passed through apoptosis induction. The expression of ER-α in MPE treated cells was same as untreated cells. MPE did  not suppress  ER-α in both nucleus and cytoplasm. Anticancer activity of MPE misht be mediated by other gene involved in ER-α signaling pathway in breast cancer cells.